Tinjauan Penerapan Pola Arsitektur Biofilik di Fasilitas Pelayanan Kesehatan Jiwa - Amanda, Putri; Winasih, Sri Suryani Yuprapti (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2025)
The impression created by the atmosphere of health facilities, especially mental health, can affect the psychological and physical state of patients. The application of biophilic architecture design in mental health care facilities is believed to help create a healing environment. Biophilic architecture inherently seeks to rebuild the relationship between humans and nature to improve human health and well-being. However, to implement biophilic design in mental health care facilities, there are criteria that must be met to ensure that the building does not have a negative impact on patients. This review was conducted to develop insights into how the application of biophilic design patterns can be applied to the interior and exterior of buildings in various mental health care facilities. The research object involves 2 mental health service facilities including Dr. Radjiman Wediodiningrat Mental Hospital in Malang and Horizon Rehab Center in Bangkok. The research method used was a descriptive qualitative method by focusing on the results of the implementation of biophilic design patterns in mental health care facilities. Analysis of the data revealed that 3 of the 14 biophilic design patterns, namely complexity & order, mystery and risk / danger, are not suitable for application in these buildings because they can have a negative effect on patients with mental disorders